2017
DOI: 10.1128/iai.00363-17
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral T-Cell Reactivity to Heat Shock Protein 70 and Its Cofactor GrpE from Tropheryma whipplei Is Reduced in Patients with Classical Whipple's Disease

Abstract: Classical Whipple's disease (CWD) is characterized by the lack of specific Th1 response toward Tropheryma whipplei in genetically predisposed individuals. The cofactor GrpE of heat shock protein 70 (Hsp70) from T. whipplei was previously identified as a B-cell antigen. We tested the capacity of Hsp70 and GrpE to elicit specific proinflammatory T-cell responses. Peripheral mononuclear cells from CWD patients and healthy donors were stimulated with T. whipplei lysate or recombinant GrpE or Hsp70 before levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The nearby generation of provocative cytokines through macrophages and endothelial cells within the fringe might actuate lymphocyte invasion through a defective endothelial obstruction taken after by central aggravation, indeed in immunologically ensured tissues such as joints or the neuronal domain (Schneider et al 2008).Currently hydroxychloroquine (600 mg/day) and doxycycline (200 mg/day) used for treatment of whipple's disease for 12-18 months, but life time follow up is required (Lagier et al 2014), so it is time consuming treatment process and only few handful trials were conducted in earlier studies (Feurle et al 2013). Nowadays epitope based vaccines provide better options in search of good treatment strategy for such type of harmful and rare malady, even if the individuals are genetically predisposed as in case of classical Whipple's disease (Trotta et al 2017). This modern approach of putative vaccine determination which involves the use of proteomic databases is very handy and easy to use method not only for rare bacterial pathogens, but also very effective in case of harmful viruses like Nipah (Kaushik 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The nearby generation of provocative cytokines through macrophages and endothelial cells within the fringe might actuate lymphocyte invasion through a defective endothelial obstruction taken after by central aggravation, indeed in immunologically ensured tissues such as joints or the neuronal domain (Schneider et al 2008).Currently hydroxychloroquine (600 mg/day) and doxycycline (200 mg/day) used for treatment of whipple's disease for 12-18 months, but life time follow up is required (Lagier et al 2014), so it is time consuming treatment process and only few handful trials were conducted in earlier studies (Feurle et al 2013). Nowadays epitope based vaccines provide better options in search of good treatment strategy for such type of harmful and rare malady, even if the individuals are genetically predisposed as in case of classical Whipple's disease (Trotta et al 2017). This modern approach of putative vaccine determination which involves the use of proteomic databases is very handy and easy to use method not only for rare bacterial pathogens, but also very effective in case of harmful viruses like Nipah (Kaushik 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, T. whipplei up-regulates the expression of DnaK upon heat shock 42 and patients with classical Whipple’s disease have reduced peripheral T-cell reactivity against DnaK compared to that of healthy controls. 43 Finally, and not surprisingly, we also identified WiSP as membrane-associated glycoproteins that bind galectins. Although their role during T. whipplei infection has not been clearly characterized, it was shown that prolonged axenic growth was associated with reduced WiSP glycosylation and impaired intracellular replication in macrophages.…”
Section: Discussionmentioning
confidence: 61%
“…The pathogenesis of Whipple's disease remains obscure and asymptomatic carriage is common (4)(5)(6)(7)(8). However, some hypothesize that underlying host immune deficiency and secondary immune downregulation induced by the bacterium play a role in the development of clinical disease (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%